Application Of Digimco Media To Improve Student's Understanding - Supriyo; Ani Afifah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The learning process will not be effective and interesting if the teacher only talks about things that happened. For that we need a media that can be manipulated, can be seen, can be heard and can be read by students. One of them is comic media. This study aims to describe learning using Digimco Media (Digital Math Comic) which can improve the mathematical understanding of class X students. This research procedure refers to the classroom action research model by Kurt Lewin which consists of problem identification, planning, implementation and observation, and reflection. The instrument used consisted of the results of working on worksheets, quizzes, final tests, teacher activity observation sheets, and student activity observation sheets. The results showed that learning with the Digimco Media could improve students' mathematical understanding. This is shown from the results of observations of teacher and student activities in the good category. In addition, the results of quizzes and final tests are also a determinant of success in this study. The quiz results in the first cycle classically reached 73.91% and the final test in the first cycle reached 65.21%. While in the second cycle the classical quiz results reached 85% and the second cycle final test reached 80%. This means that the research carried out is said to be successful in accordance with the established success criteria.